2018
DOI: 10.1007/s00420-018-1288-5
|View full text |Cite
|
Sign up to set email alerts
|

Interaction effect of job insecurity and role ambiguity on psychological distress in Japanese employees: a cross-sectional study

Abstract: PurposeWe examined the interaction effect of job insecurity (JI) and role ambiguity (RA) on psychological distress in Japanese employees.MethodsOverall, 2184 male and 805 female employees from two factories of a manufacturing company in Japan completed a self-administered questionnaire comprising the scales measuring JI (Job Content Questionnaire), RA (National Institute for Occupational Safety and Health Generic Job Stress Questionnaire), psychological distress (K6 scale), and potential confounders (i.e., age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 53 publications
0
18
0
1
Order By: Relevance
“…A self-report questionnaire administered to 66 health professionals in Italy showed that role ambiguity constituted a psychosocial deficit that influenced workers’ wellbeing and led to emotional exhaustion [ 62 ]. In a cross-sectional study conducted on 2989 Japanese employees, work ambiguity was associated with psychological distress and even mediated the relationship between job insecurity and psychological distress [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…A self-report questionnaire administered to 66 health professionals in Italy showed that role ambiguity constituted a psychosocial deficit that influenced workers’ wellbeing and led to emotional exhaustion [ 62 ]. In a cross-sectional study conducted on 2989 Japanese employees, work ambiguity was associated with psychological distress and even mediated the relationship between job insecurity and psychological distress [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Job security can be defined as an employee’s fear of losing their job and being unemployed ( De Witte, 1999 ). Job insecurity is an important factor that impairs the psychological health of employees ( Nella et al, 2015 ; Inoue et al, 2018 ) and reduces motivation ( Ünsar, 2011 ). Job engagement can be defined as a positive and fulfilling state that is characterized by the vigor, and absorption of employees ( Schaufeli et al, 2002 ).…”
Section: Literature Review and Conceptual Modelmentioning
confidence: 99%
“…Many authors define job insecurity as employees' expectations of continuing to work (Davy et al, 1997;Sverke et al, 2002;De Witte, 1999), whereas others define job insecurity as employees' perceptions of the probability of losing their jobs in moments of crisis (Mohr, 2000). Job insecurity is a major factor that affects the psychological health of employees (Inoue et al, 2018) and tends to diminish their motivation (Unsar, 2011). However, job insecurity implies uncertainty about the future, since employees are unsure if they will stay or lose their current position, or whether they should explore for new opportunities.…”
Section: Job Insecuritymentioning
confidence: 99%